Investment treaty reform when regulatory chill causes global warming - Henrik Horn (Research Institute of Industrial Economics (IFN), 2023)
It is often claimed that investment treaties will dissuade host countries from phasing out foreignowned CO2-intensive production. This paper uses a very simple economic framework to examine how such a problem might be alleviated through treaty reform, including increased carve-outs from compensation requirements, reduced compensation in case of regulation, exclusion of ISDS, and a shortened sunset clause in case of withdrawal/termination. While all reforms can address the stranded investment problem in certain circumstances, they either fail in other circumstances, or will not be accepted by both parties, suggesting a trade-o between effi cacy and acceptability of the reforms.
Keywords: F21; F23; F53; K33; 330; Investment treaties; climate; stranded assets; regulatory chill